One-pot Multicomponent Synthesis of Hydrazinyl Thiazoles Bearing an Isatin Moiety in Aqueous Medium - Sim, Kooi-Mow; Chung, Li-Ping; Tan, Kit-Lin; Tan, Yee-Ting; Kee, Xin-Lee; Teo, Kah-Cheng (Letters in Organic Chemistry, 2024)
Isatin-derivatives are an important class of nitrogen-containing heterocyclic compounds in organic synthesis. On the other hand, 1,3-thiazoles are 5-membered heterocyclic compounds containing nitrogen and sulphur atoms. Hydrazinyl thiazoles are often prepared through the classical condensation of aldehydes or ketones with thiosemicarbazide to yield thiosemicarbazones, which will then undergo heterocyclization with phenylacyl bromides to give the corresponding hydrazinyl thiazoles. Nowadays, multi-component reactions (MCRs) are considered the most powerful tool in organic synthesis. The use of water as a green solvent in organic synthesis is one of the goals of green chemistry. In this study, a series of new hydrazinyl thiazoles 3a-3u bearing an isatin moiety were synthesized in good yield via a one-pot three-component condensation reaction of isatins with thiosemicarbazide and phenyl acyl bromides in water under reflux condition. All the synthesized compounds were characterized by IR, 1D-NMR, 2D-NMR and LC/MS spectral data.
Keywords: One-pot synthesis